2009
DOI: 10.1128/jcm.00155-09
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Nationwide Study of Aeromonas Infections in France

Abstract: We report a systematic prospective multicenter nationwide study of clinical Aeromonas infections in France. During 6 months (May to October 2006), 78 cases of aeromonosis were reviewed for risk factors and clinical, microbiological, and antimicrobial susceptibility data. They included wound infections (44%), bacteremia (26%), enteritis (19%), respiratory tract infections (6%), and miscellaneous (5%) infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
99
6
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(113 citation statements)
references
References 35 publications
6
99
6
2
Order By: Relevance
“…Aeromonas and Vibrio were more commonly associated with skin infections than gastroenteritis in our setting, which has been previously reported 8 in contrast to some other studies. 16 Factors that may explain this are the high standards of safe drinking water available to our population and water temperatures that favor year-round growth of these organisms in recreational areas.…”
Section: Discussioncontrasting
confidence: 90%
“…Aeromonas and Vibrio were more commonly associated with skin infections than gastroenteritis in our setting, which has been previously reported 8 in contrast to some other studies. 16 Factors that may explain this are the high standards of safe drinking water available to our population and water temperatures that favor year-round growth of these organisms in recreational areas.…”
Section: Discussioncontrasting
confidence: 90%
“…A 1996 study of antibiotic susceptibility in clinical isolates of Aeromonas in Taiwan (5) concluded that certain cephalosporins (moxalactam, ceftazidime, and cefepime), amikacin, aztreonam, imipenem, and quinolones were reasonable choices for empirical treatment. A 2009 study of Aeromonas in France recommended that a cephalosporin or a quinolone be prescribed along with an aminoglycoside in cases of severe infection (6). We believe that the reported emerging resistance of Aeromonas to quinolones (1,10) and carbapenems (7,11), as well as aztreonam, cephalosporins, and aminoglycosides (this report), might influence physicians to employ polytherapy for empirical treatment of severe Aeromonas hydrophila infections.…”
mentioning
confidence: 79%
“…The first group involves major trauma, the most common of which is near-drowning events, of which there are an estimated 16,000 to 160,000 instances in the United States annually (69). Recent cases of Aeromonas pneumonia accompanying septicemia have been linked to near-drowning events involving seawater (217), a shallow irrigation ditch, and other massive aquatic exposures (178,209). The rapid demise of patients in this setting can be as quick as 9 h from the initial insult to time of death (209).…”
Section: Respiratory Tract Infectionsmentioning
confidence: 99%